Determinants of Surgical Instrument Counting Compliance in The Central Surgical Installation - sri lestari; Istiatin Istiatin; Ikhwan Hamzah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to To determine factors influencing compliance in surgical instrument counting, specifically knowledge, attitude, workload, and leadership leadership in the Central Surgical Unit of Dr. Moewardi Regional General Hospital. This research method used cross-sectional study was conducted at the Central Surgical Installation of Dr. Moewardi Regional Hospital from July to August 2025. The study population included all surgical nurses, with a sample of 90 selected using a total sampling technique. The dependent variable was the level of compliance in surgical instrument counting. The independent variables were knowledge, attitude, workload, and leadership. Data were collected through a questionnaire. Data analysis was performed using univariate tests, bivariate tests (Spearman Rank), and multivariate analysis (multiple linear regression) to examine the simultaneous and partial effects of independent variables on compliance. The Results Multivariate analysis showed that knowledge and attitude significantly influenced compliance in surgical instrument counting. Meanwhile, workload and leadership did not show a significant effect. The regression model explained 40.45% of the variation in compliance. Conclusion: Increasing knowledge and developing positive attitudes are crucial for improving nurse compliance in surgical instrument counting. Workload and formal leadership did not have a significant effect in the context of this study. It is recommended that institutions prioritize ongoing training and fostering a culture of patient safety to support compliance.